Potensi Kompos, tepung Azolla dan Dedak sebagai bahan Pembawa Bakteri Pemfiksasi N (BPN) dalam meningkatkan pertumbuhan dan hasil gabah Padi Gogo pada Inceptisols Jatinangor - Pujawati Suryatmana; Jihan Fitria Meilani; Nadia Nuraniya Kamaluddin; Tualar Simarmata (Soilrens, 2022)
Rice is an important commodity in Indonesia because rice is the main source of carbohydrates for the Indonesian. Rice production in Indonesia relies on lowland rice, but the productivity of lowland rice is decreasing. One of the efforts to increase rice national production is utilizing upland rice plants. The problem with upland rice is its low productivity. Nitrogen-fixing biological fertilizers can be used to increase the productivity of upland rice plants. The effect of different doses of nitrogen fertilizer and nitrogen fixing bacteria with different carrier materials on the growth and yield of upland rice in Inceptisols Jatinangor was studied. Randomized block design with two factors: the recommended dose of urea fertilizer (100% and 50%) and the nitrogen-fixing bacteria factor with different carriers (compost, rice bran, and Azolla powder) were applied as an experimental design. The experimental results showed that the interaction of nitrogen fertilizer dose and nitrogen-fixing bacteria with different carriers had no significant effect on plant height, number of panicles, root shoot ratio, and weight of 1000 grains of upland rice plants. Application of nitrogen-fixing bacteria with compost, bran, and Azolla powder as carriers was able to increase the average weight of the filled grain higher than the control.